Manajemen Sarana dan Prasarana dalam Meningkatkan Proses Pembelajaran Siswa Kelas XI Akuntansi dan Keuangan Lembaga SMK 17 Seyegan Kabupaten Sleman - Eka Yulianta (Journal on Education, 2023)
Facilities and infrastructure are important components in determining the success of the educational process and one of the factors in improving the quality of education in Indonesia. The importance of educational facilities and infrastructure makes every educational institution make every effort to meet the standards of educational facilities and infrastructure to improve the quality of the learning process. This research uses a qualitative approach with descriptive analysis. The research subjects were school principals, teachers, administrative staff, and school heads of the Sarpras section of schools. The data collection technique used is the interview method, the observation method, and the documentation method, which will later obtain primary and secondary data to then be analyzed together to draw conclusions. Based on the results of the research that the authors have done, it can be concluded that the management of infrastructure facilities at SMK 17 Seyegan in supporting the learning process is quite good. However, some of the management of facilities and infrastructure has not been realized, including in the process of planning, procurement, use, maintenance and elimination of infrastructure facilities. The constraints experienced were the lack of human resources in administration and infrastructure as well as incoming funds for the procurement process and infrastructure management processes which were still slow